NUMERICAL MODELING OF CONTAMINATING SUBSTANCES DISTRIBUTION IN RESIDENTIAL AREAS - A.A. Issakhov; A. Abay; P.T. Omarova; Zh.E. Bekzhigitova (Academic Scientific Journal of Computer Science, 2019)
In this study, a numerical simulation of the contaminants distribution in a street canyon and the effect of barriers on this process were carried out. To solve this problem, a Reynolds-averaged Navier-Stokes equation was used. To solve this problem, a turbulent DES model was used, which showed good results for the test problem. To test the mathematical model and the numerical algorithm, the test problem was solved. The obtained numerical results were compared with experimental data and the results of modeling by other authors. After checking the mathematical model and the numerical algorithm, the main problem was described considering the process of pollutant emission between houses using different barrier heights. As a computational area, a model of a street canyon was taken with a ratio of sides that ranged from 0.05 m to 0.2 m. As shown by numerical modeling, the presence of barriers leads to the appearance of an additional vortex in the space between objects, which increase as their height increases. As a result, it can be observed that most of the contaminants are trapped between them. In the course of various studies it was revealed that the presence of barriers along the roads reduces the concentration of harmful substances in the air. So when using a grass barrier height of 0.1 m, the concentration value falls into the section x=0.05 m more than 1.5 times as compared without using barriers. Thus, it can be said that barriers provide good filtration of polluted air, which has a detrimental effect on the environment and human health.